Global, regional, and national burden of lung cancer attributable to second-hand smoke from 1990 to 2021: a systematic analysis based on the Global Burden of Disease Study 2021 - Zhang, Zheng; Zhang, Xiao-hui; Huang, Rong; Fan, Jia-jia; Ma, Xue-jiao; Jin, Zi-han; Wang, Qin; Li, Yu-long; Su, Fei (Frontiers in Oncology, 2025)
IntroductionSecond-hand smoke (SHS) exposure significantly contributes to lung cancer development, yet its global burden remains poorly quantified.MethodUsing data from the Global Burden of Disease Study 2021, we analyzed SHS-related lung cancer deaths, disability-adjusted life-years (DALYs), and corresponding age-standardized rates (ASRs) across different regions and countries, stratified by gender, age, and Socio-Demographic Index (SDI). The estimated annual percentage changes (EAPCs) in the ASRs were calculated to determine the temporal trends spanning from 1990 to 2021. We also quantified the relationship between the SDI and the age-standardized rates of lung cancer caused by SHS.ResultsIn 2021, SHS accounted for approximately 0.10 million lung cancer deaths and 2.37 million DALYs worldwide, with a male-to-female mortality ratio of 1.38. The age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) manifested a trend of decline, with EAPC of -0.88 (95% UI: -0.94 to -0.82) and -1.25 (95% UI: -1.31 to -1. 19), respectively. The ASMR or ASDR peaked in middle and high-middle SDI regions, with a lower burden in other SDI regions. Nevertheless, the ASMR and ASDR in the high SDI region witnessed the most significant decline. Men bore a heavier burden of lung cancer attributable to SHS compared with women. The sexual disparity was more conspicuous among the elderly.ConclusionDuring the past 32 years, the global burden of lung cancer attributable to SHS has revealed a downward tendency, concomitant with a decline in SHS exposure. The rise in absolute deaths and DALYs is driven by population growth and aging despite falling ASRs. Persistent epidemiological disparities across genders, age groups, and regions underscore the need for targeted interventions, particularly in middle and high-middle SDI settings.